Mini marvels: superhero engagement across early childhood - Coyne, Sarah M.; Ashby, Sarah; Munk, Rachel J.; Holmgren, Hailey G.; Shawcroft, Jane; Densley, Rebecca; Austin, Tanya; Banks, Kennedy; Van Alfen, Megan (Frontiers in psychology, 2025)
Superhero engagement is common in early childhood, particularly among boys, and tends to be related to negative outcomes, such as aggression. However, most research lumps all types of superhero engagement together and is conducted over a relatively short space of time. The current study is a five-year longitudinal study of four different types of superhero engagement (identification, toys, dress up, and media). Participants included 430 children ( age = 29.17 months at Wave 1) and their primary caregivers who were asked questions about superhero engagement and social behavior once a year for 5 years. Overall, superhero engagement was relatively high in early childhood and showed distinct trajectories depending on the type of engagement, with the most rapid growth occurring in superhero media. Boys and those who viewed high levels of television were more likely to have higher levels of superhero engagement. Additionally, early high identification with superheroes and playing with superhero toys and moderate but increasing superhero media predicted higher levels of aggression and aggressive defending over time. Dressing up as superheroes was related to very few outcomes during early childhood. Overall, this study has implications for parents, educators, and creators of superhero media and merchandise.